MSME Entrepreneurship Promotion Training Through On-line Applications and Global Social Media: Pelatihan Promosi Wirausaha UMKM Melalui Aplikasi On-line dan Media Sosial Global - Widiarto, Wisnu; Wiharto, Wiharto; Salamah, Umi; Suryani, Esti (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Technological advances have had an impact on various fields. Likewise for UMKM entrepreneurs in Gadingan-Mojolaban-Sukoharjo, to promote karak and romeo businesses. This community service program has been implemented by means of socialization, training and mentoring to UMKM entrepreneurs in Gadingan Village, regarding on-line e-commerce applications, and social media. Preliminary analysis of partners has shown problems that occur in UMKM entrepreneurs, namely a lack of understanding of on-line applications and global social media. Implementation of socialization, training and mentoring for partners has been carried out to empower UMKM entrepreneurs. It is expected that partners can follow the flow of technology and be able to face competition in this digital technology era. With increased competition, UMKM entrepreneurs are required to be able to face all challenges. This can be done by increasing product innovation and expanding marketing networks, promotions and publications about their business. The method that has been used is to provide socialization-training- mentoring in promoting and registering businesses in on-line applications and global social media.